ANALISIS PENGARUH MULTI ATRIBUT PRODUK TERHADAPKEPUTUSAN PEMBELIAN KONSUMEN MELALUI ONLINE SHOPBLACKBERRY - Lusiana Ali (2013)
This study aims to determine and prove the significant influence of multiattribute products (product quality, features and design) on consumer purchasing decisions through the online shop blackberry. By using simple regression analysis. Sample was taken from the students of UPN "VETERAN" JAKARTA especially the Faculty of Economics and Management who uses blackberry. By using SPSS 21. This study used a sample of 130 respondents, 30 and 100 research trials. The results showed that the product, price, place and promotion have strong relationships and positive impact on customer loyalty. The results achieved in this study is expected to be a material consideration for the company's progress and useful for writers as well as those reading this paper